Indonesia Legal Analysis of IUU Fishing And Transnational Organized Fisheries Crimes: Loopholes and Proposed Measures - Mubarok, Zaki (UI Scholars Hub, 2019)
The fight against illegal fishing by the Ministry of Marine Affairs and Fisheries has taken off. When investigating Illegal, Unreported and Unregulated (IUU) fishing, related transnational crimes activities such as trafficking in persons, slavery and drugs are also uncovered. In spite of the robust efforts and prompt responses, some challenges persist in terms of the inadequacy of legal frameworks governing these problems. Thus, the adequacy of the legal domain is a significant factor in pursuing the Ministry’s mission. The legal framework plays a pivotal role in addressing IUU fishing and transnational organized fisheries crimes and in setting a mechanism to prevent further expansion of these activities. In developing an in-depth analysis of the nexus between IUU fishing and transnational organized crimes, the two dimensions of intertwined national and international legal frameworks need to be examined. This article attempts to examine the existing Indonesian legal framework to combat IUU fishing and fisheries crimes within the context of relevant national and international laws and provide a critical discussion of the interplay between IUU fishing and transnational organized crimes.